Feeding of the scyphomedusa Stomolophus meleagris in the coastal lagoon Las Guásimas, northwest Mexico - Padilla-Serrato, Jesús Guadalupe; López-Martínez, Juana; Acevedo-Cervantes, Alejandro; Alcántara-Razo, Edgar; Rábago-Quiroz, Carlos Hiram (HIDROBIOLÓGICA, 2017)
The cannonball jellyfish (S. meleagris) has reached production levels that has led it to become an important fishery resource in Las Guásimas, Sonora, a coastal lagoon in northwestern Mexico; however, its ecological importance and role in the ecosystem remain unstudied. This contribution describes the diet composition of this species in order to reveal its trophic importance in this coastal lagoon. Up to 17 jellyfish were captured in each of three surveys (March 2008, February and April 2009), their stomachs were extracted and analyzed to determine their diet composition. The quantitative methods: frequency of occurrence (F), numeric (N), gravimetric (W) and the index of relative importance, were used to measure the diet components, and Levin´s index to measure the diet amplitude. Thirteen preys were identified; all belonging to the zooplankton community; the most important prey were the anchovy eggs. Our results show that S. meleagris is a specialist predator (with a marked preference for certain prey), classified in the third trophic level (3.2), as a secondary consumer.